Visual Asset Punk Surrealistic Independent Music Label: Warkop Musik Bandung - Aulia, Rahmiati; Bastari, Rendy Pandita; Resmadi, Idhar (Program Studi Desain Komunikasi Visual. Fakultas Arsitektur dan Desain Jalan Raya Rungkut Madya, Gn.Anyar, Surabaya, Jawa Timur 60294, 2024)
Warkop Musik supports the independent music movement as an independent Bandung record label. However, there are challenges faced in the form of a lack of merchandise diversification, which results in limited market reach. Previous research shows that merchandise can improve SME business performance through various public channels and online platforms. Public procurement has an important role in accessing markets and increasing the growth of Small and Medium Enterprises (SMEs). Heskett's design method is used to link industrial design with economics. The research data collection process includes literature study, observation and interviews. The design process starts from sketching, finalizing and evaluating visual assets. The visual style applied is a surreal, cartoon-style illustration. The results of the research show that a diversification strategy through merchandise with a design approach can expand Warkop Musik's market reach and improve its business performance.